2013
DOI: 10.1111/nph.12102
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural leaf carbohydrate dynamics of Pinus edulis during drought‐induced tree mortality reveal role for carbon metabolism in mortality mechanism

Abstract: SummaryVegetation change is expected with global climate change, potentially altering ecosystem function and climate feedbacks. However, causes of plant mortality, which are central to vegetation change, are understudied, and physiological mechanisms remain unclear, particularly the roles of carbon metabolism and xylem function.We report analysis of foliar nonstructural carbohydrates (NSCs) and associated physiology from a previous experiment where earlier drought-induced mortality of Pinus edulis at elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(182 citation statements)
references
References 88 publications
10
160
1
Order By: Relevance
“…Some of the unexplained variation may be caused by our inability to include topoedaphic and plant community effects as well as other potentially useful traits because of lack of data. In particular, it would be valuable to examine the level and utility of carbon reserves during drought, which were related to mortality in some studies (28,29) but not in others (14,30). Currently, however, enormous methodological uncertainty with nonstructural carbohydrates measurements prohibits cross-study comparison (31).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the unexplained variation may be caused by our inability to include topoedaphic and plant community effects as well as other potentially useful traits because of lack of data. In particular, it would be valuable to examine the level and utility of carbon reserves during drought, which were related to mortality in some studies (28,29) but not in others (14,30). Currently, however, enormous methodological uncertainty with nonstructural carbohydrates measurements prohibits cross-study comparison (31).…”
Section: Resultsmentioning
confidence: 99%
“…2009; Adams et al. 2013). On the other hand, drought could decrease a tree's carbon demand by downregulating growth, leading to a sink limitation, and in some cases, increased allocation to storage (Sala et al.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies reported widespread reductions of growth and increased mortality worldwide, which affect several tree species and biomes, including tropical forests (Fisher et al 2007), temperate mountain conifer and hardwood forests (Linares & Camarero 2012, Anderegg et al 2013, drought-prone mountain conifer forests (Adams et al 2013), Mediterranean conifer forests (Linares et al 2009) and Mediterranean oak forests (Lloret et al 2004, Camarero et al 2015a, 2015b.…”
Section: Introductionmentioning
confidence: 99%